2009
DOI: 10.2140/agt.2009.9.537
|View full text |Cite
|
Sign up to set email alerts
|

Infinitesimal rigidity of a compact hyperbolic 4–orbifold with totally geodesic boundary

Abstract: Kerckhoff and Storm conjectured that compact hyperbolic n-orbifolds with totally geodesic boundary are infinitesimally rigid when n > 3. This paper verifies this conjecture for a specific example based on the 4-dimensional hyperbolic 120-cell.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Hyperbolic d-space. Lorentzian (d + 1)-space R d,1 is a (d + 1)-dimensional real vector space equipped with the Lorentzian inner product (1) x, y…”
Section: Preriminaliesmentioning
confidence: 99%
See 3 more Smart Citations
“…Hyperbolic d-space. Lorentzian (d + 1)-space R d,1 is a (d + 1)-dimensional real vector space equipped with the Lorentzian inner product (1) x, y…”
Section: Preriminaliesmentioning
confidence: 99%
“…Kerckhoff, Storm, and Aougab studied rigidity of RACGs with Fuchsian ends and showed that the followings: first, Aougab and Strom showed that the RACGs with Fuchsian ends obtained from the compact right-angled 120-cell group are locally rigid [1]. After that, Kerckhoff and Storm generalized the result to convex cocompact ddimensional RACGs with Fuchsian ends for d ≥ 4 [6].…”
Section: The Upper Half-spacementioning
confidence: 99%
See 2 more Smart Citations
“…This group produces an orbifold quotient of H 4 with totally geodesic boundary in a suitable orbifold sense. Again starting with the hyperbolic 120-cell, Aougab and the second author verified Theorem 1.1 for a specific group generated by reflections in 96 walls of the hyperbolic right-angled 120-cell [1]. These 96 walls were chosen so the complementary 24 walls form a maximal collection of pairwise disjoint walls.…”
mentioning
confidence: 97%